2023
DOI: 10.1101/2023.05.22.541721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery from anhydrobiosis in the tardigradeParamacrobiotus experimentalis: better to be young than old and in a group than alone

Abstract: Desiccation-tolerant organisms can survive dehydration in a state of anhydrobiosis. Tardigrades can recover from anhydrobiosis at any life stage and are considered among the toughest animals on Earth. However, the factors that influence recovery from anhydrobiosis are not well understood. The study aimed to evaluate the effect of sex, age, occurrence in a group and the combination of the number and duration of anhydrobiosis episodes on the recovery of Paramacrobiotus experimentalis. The activity of 1,200 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…experimentalis revealed that the recovery from anhydrobiosis is influenced by several factors. These include age, the combination of the number and duration of anhydrobiosis episodes, and the presence of other individuals [56]. The current study demonstrated that none of the tested concentrations of ibuprofen had a significant impact on the recovery from anhydrobiosis of Pam.…”
Section: Discussionmentioning
confidence: 57%
“…experimentalis revealed that the recovery from anhydrobiosis is influenced by several factors. These include age, the combination of the number and duration of anhydrobiosis episodes, and the presence of other individuals [56]. The current study demonstrated that none of the tested concentrations of ibuprofen had a significant impact on the recovery from anhydrobiosis of Pam.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that the length of exposure to HMF may be an important factor for the observed effect (Sinčák and Sedlakova-Kadukova, 2023) Moreover, it appears that the tardigrade's ability to survive under extreme conditions can be influenced by many factors (e.g., McCarthy and delBarco-Trillo, 2020). Our previous results indicate that age and sex could be important to tardigrades' survival under extreme conditions represented by water deficiency resulting in dehydration (Nagwani et al, 2023). Therefore, we decided to study the impact of different durations of exposure to HMF on the survival rate and mitochondrial Δψ levels of active tardigrades of different ages and sex.…”
Section: Introductionmentioning
confidence: 77%
“…Females and males of P. experimentalis (Kaczmarek et al, 2020;Nagwani et al, 2023) were reared together in covered, vented plastic Petri dishes (55 mm in diameter), with the bottom scratched with sandpaper to allow the animals to move. The individuals were coated with a thin layer of the culture medium, a mixture of spring water (Żywiec Zdrój S.A., Poland), and ddH2O in a 1:3 ratio.…”
Section: Cultures Of Paramacrobiotus Experimentalismentioning
confidence: 99%